Sukur Kingdom: The Sleeping Beauty (Popularizing Nigeria’s 1st UNESCO World Heritage Site) - Oladimeji, Oluwasegun M.; Umaru, Isaac John (Kwaghe International Journal of Arts, Humanities and Religious Studies, 2024)
The Sukur Kingdom, located in Madagali Local Government Area of Adamawa State, Nigeria, is recognized as a UNESCO World Heritage Site for its unique cultural landscape, ancient iron smelting technology, and terraced fields. Despite its historical significance, the site remains largely unknown to the global and local audience. This paper seeks to explore the cultural, historical, and geographical attributes of the Sukur Kingdom, examining its potential as a key tourist attraction. By identifying the challenges facing its promotion, this article proposes strategies for popularizing the site while preserving its heritage.